2017
DOI: 10.1002/mnfr.201600943
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet and associated changes in the expression of micro‐RNAsin tissue: Lessons learned from animal studies

Abstract: Environment and genetic factors play an important role in the development of obesity, and diet is one of the main contributing factors to this disease. High fat intake is associated with body weight gain, leading to obesity and other metabolic diseases. MicroRNAs (miRNAs) are a group of small, noncoding RNAs that are important regulators of gene expression at posttranscriptional level. Studies have shown that high fat intake, independent of body weight status, can significantly impact both negatively and posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 151 publications
(225 reference statements)
0
14
0
Order By: Relevance
“…Obesity is defined as an excessive accumulation of fat in adipose tissue that increases the risk of non‐transmissible diseases such as diabetes, cardiovascular events, and certain types of cancer . In an obese condition, it is desirable to reduce adipocyte differentiation rate in order to reduce fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is defined as an excessive accumulation of fat in adipose tissue that increases the risk of non‐transmissible diseases such as diabetes, cardiovascular events, and certain types of cancer . In an obese condition, it is desirable to reduce adipocyte differentiation rate in order to reduce fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is defined as an excessive accumulation of fat in adipose tissue that increases the risk of non-transmissible diseases such as diabetes, cardiovascular events, and certain types of cancer. [22,23] In an obese condition, it is desirable to reduce adipocyte differentiation rate in order to reduce fat accumulation. For the first time, the effects of a well-characterized anthocyaninrich extract from purple corn in 3T3-L1 adipocytes differentiation was evaluated in comparison to pure anthocyanins.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study showed that adequate dietary intake prevents against UWL, although it is not associated with better functional state . In this regard and considering the need to initiate a prospective nutritional intervention study in symptomatic patients, a customized HD‐diet was designed to determine whether proper feeding is capable of preventing UWL associated with the disease, modifying the miRNAs HD‐footprint and inducing an improvement in neurological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding with an obesogenic diet will alter the expression of specific miRNAs related to lipid metabolism. For example, the expression of miRNA-122 was decreased by a high-cholesterol diet in minipigs; miR-143 expression was significantly increased on the high fat diet [ 17 , 18 , 19 ]. In addition, miR-143 expression levels were correlated with PPARγ and aP2, genes which regulate adipocyte differentiation and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%